Webcams, Songs, and Vocabulary Learning: A Comparison of In-Person and Remote Data Collection as a Way of Moving Forward With Child-Language Research - Morini, Giovanna; Blair, Mackensie (Frontiers in Psychology, 2021)
This article evaluates a testing procedure for collecting eye-gaze data with toddlers and preschoolers during a word-learning task. We provide feasibility and precision data by comparing performance in an in-person version of the study (conducted under controlled conditions in the lab), with performance in a virtual version in which participants completed the testing procedure from home. Our data support the feasibility of collecting remote eye-gaze data with young children, and present it as a viable alternative for conducting developmental language research when in-person interactions with participants cannot take place. Additionally, we use this methodological approach to examine a topic that has gained popularity in recent years – the role of music and songs on vocabulary learning. We provide evidence suggesting that while songs may help increase attention during a particular task, greater attention does not lead to greater learning. In fact, preschoolers show improved word-learning performance for items that were trained in a spoken sentence compared to items that were trained in a song. This means that while songs may be beneficial for increasing child engagement, spoken sentences may be best for supporting deep level learning of language concepts.